P-007 Incidence and Management of Intimal Hyperplasia at 6 months after Flow Diversion for Intracranial Aneurysms. (26th July 2014) - Massari, F; Puri, A; Hou, S; Perras, M; Brooks, C; Stout, C; Gounis, M; Wakhloo, A
Abstract : Introduction/purpose: A new option in the treatment of large and complex intracranial aneurysms centerd along the cavernous/intradural segment of the ICA, proximal to the PCom artery, includes the utilization of flow-diverter devices. Intracranial stent/ flow diverter deployment in the treatment of aneurysm usually requires the administration of dual antiplatelet therapy for 3–12 months. Our usual protocol is to switch to mono-therapy with Aspirin after 6 months. We analyzed the results after continuing dual anti-platelet therapy based on the intimal hyperplasia (IH) noted on the 6 month follow-up cerebral angiography. The purpose of this study is to assess at 1-year follow-up the efficacy of mono or dual antiplatelet therapy in the management of in-PED IH observed at the 6-month cerebral angiogram. Materials and methods: From October 2011 to February 2014, a total of 93 intracranial aneurysms in 83 patients (16 men and 67 women; age range, 19–85 years; mean age, 56.6 years) were treated with pipeline embolization device (PED) at our institution. A cone-beam CT (Philips, Allura Biplane FD20/20, Philips Medical, Best, Netherlands) was obtained using the angiography C-arm to assess for IH at FU angiographies. At 6-month follow-up (39 patients with 46 aneurysms) 8 cases of in-PED no-flow limiting minimal IH (< 10% vessel stenosis) were noted. In these patients medical management using continuation of dual antiplatelet therapy for additional 6 months up to a 1 year cerebral angiogram follow-up was used. Results: In the 8 patients having IH at the 6 months angiogram, 4 patients have till now underwent a 1 year follow-up. Complete resolution of the intimal hyperplasia was seen in 3 patients, whereas a stable IH was noted in one patient. One year follow up angiography was available for an additional 11 patients, who did not have IH at the 6 month FU. The 1 year FU angiography in these patients demonstrated no interval development of IH after stopping Clopidogrel at the 6 month time period. Conclusion: In our experience the adjustment of antiplatelet drug therapy post endovascular PED treatment of intracranial aneurysm depending on 6 month follow up findings is strongly associated with complete Pipeline Embolization Device patency at 1-year follow-up. Furthermore in our experience cone-beam CT is an accurate and precise tool in the assessment of in-PED intimal hyperplasia development during follow-up. Disclosures: F. Massari: None. A. Puri: None. S. Hou: None. M. Perras: None. C. Brooks: None. C. Stout: None. M. Gounis: None. A. Wakhloo: None.